Efficacy of blood glucose self-monitoring on glycemic control in patients with non-insulin-treated type 2 diabetes: A meta-analysis - Yun-Ying Hou; Wei Li; Jing-Bo Qiu; Xiao-Hua Wang (Elsevier, 2014)
Objective: To evaluate the efficacy of blood glucose self-monitoring on glycemic control in patients with non-insulin-treated type 2 diabetes by performing a meta-analysis. Methods: Randomized controlled trials (RCTs) of the efficacy of blood glucose self-monitoring were collected from the PubMed, EMBASE, Cochrane Library, CNKI, and VIP databases. Data were analyzed by RevMan 5.1 software. Results: Seven RCTs were included in this meta-analysis. The results indicated that blood glucose self-monitoring significantly reduced the glycated hemoglobin (HbA1c) level by 0.41%. Subgroup analysis showed that while implementation of a diabetes management regimen based on the blood glucose self-monitoring results effectively reduced the HbA1c level by 0.42%, no significant improvement in HbA1c level control was observed with the implementation of blood glucose self-monitoring alone. Conclusion: Blood glucose self-monitoring combined with diabetes management effectively improves glycemic control in patients with non-insulin-treated type 2 diabetes.